2013
DOI: 10.3109/00952990.2013.836531
|View full text |Cite
|
Sign up to set email alerts
|

Crystal methamphetamine initiation among street-involved youth

Abstract: Background Although many settings have recently documented a substantial increase in the use of methamphetamine-type stimulants, recent reviews have underscored the dearth of prospective studies that have examined risk factors associated with the initiation of crystal methamphetamine use. Objectives Our objectives were to examine rates and risk factors for the initiation of crystal methamphetamine use in a cohort of street-involved youth. Methods Street-involved youth in Vancouver, Canada, were enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Previous studies using data from the same cohort have found high rates of crystal methamphetamine use , and in the current study, daily crack and daily crystal methamphetamine use accounted for a large proportion of baseline‐reported stimulant use. The cheap and easy access to crystal methamphetamine has been suggested to be a driver in the high rates of usage in this population .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using data from the same cohort have found high rates of crystal methamphetamine use , and in the current study, daily crack and daily crystal methamphetamine use accounted for a large proportion of baseline‐reported stimulant use. The cheap and easy access to crystal methamphetamine has been suggested to be a driver in the high rates of usage in this population .…”
Section: Discussionmentioning
confidence: 99%
“…The cheap and easy access to crystal methamphetamine has been suggested to be a driver in the high rates of usage in this population . Among youth and adult populations of PWUD, crystal methamphetamine and crack cocaine use have also been found to be associated with a higher risk profile, including risky sexual practices and HIV incidence . Taken together, it is unclear if factors that may pre‐dispose individuals to use stimulants play a role in increased risk of relapse or if characteristics of stimulant drugs and the absence of pharmacotherapy treatment modalities for stimulant dependence primarily account for this observed relationship.…”
Section: Discussionmentioning
confidence: 99%
“…While many people who use drugs are known to engage in drug dealing to sustain their drug use, 19,20 for some individuals, drug market involvement preceded the initiation of illicit drug use, which may be the case for some street-involved youth. 12,21 Among street-involved youth engaging in drug dealing in this setting, the majority (79%) have been shown to assume a role of a direct drug seller, followed by a “middler” (i.e., coordinating a deal between a dealer and client) (28%) and a “holder” (i.e., carrying drugs during a drug trade) (6%). 19 All these roles operate at the lowest end of the drug market hierarchy and thereby increase vulnerability to violence, including encounters with violent customers or police officers, and the risk of being punished when unable to fulfill assigned quotas.…”
Section: Discussionmentioning
confidence: 99%
“…As in a previous study, sex work was defined as having exchanged sex for gifts, food, clothing, shelter, money or drugs. 12 …”
Section: Methodsmentioning
confidence: 99%
“…Longitudinal research on adolescent antecedents of amphetamine use among adolescents and young adult is very limited. Most research is based on cross-sectional data, with study participants derived primarily from high-risk populations such as adult drug users (e.g., Quinn et al, 2013), or street-involved young people (e.g., Uhlmann et al, 2014). Findings from these studies have limited generalizability to the broader population, and the cross-sectional studies (e.g., Chen et al, 2014) Identification of key adolescent markers of regular use potentially provides important information for prevention and intervention programs to target high-risk adolescents at an earlier stage, reducing their risks of progressing to regular use and dependence.…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%